Medicina delle dipendenze e psicoterapia. Realtà attuali e nuove prospettive in una struttura territoriale - Magherini, Filippo (Il sogno della farfalla, 2020)
This article describes everyday clinical practice in an Addiction Service located in the Italian region of Tuscany. This place of low-threshold institutional treatment, often crowded, without any filter is a reality where medical practice is performed in close relation with the territory, through a complex net of local agencies in which many different professionals collaborate. The author highlights the need to think of a psychotherapeutic dimension able to fuse theory and practice in the attempt to answer the question of how and when a public psychotherapy would be possible. By doing so a new debate not only on the processes but also on new cultural ideas would be encouraged.